Editorial: Data-driven innovations in policy-oriented freight transport models and planning methods - Gonzalez-Feliu, Jesus; Goodchild, Anne; Guerrero, David (European Journal of Transport and Infrastructure Research, 2016)
Freight transport is a challenging economic sector, as it is essential for the functioning of production and distribution systems but and the same time is at the origin of many nuisances such as congestion, greenhouse gas emissions, pollution and noise. When responding to these issues, planners dispose nowadays of a growing body of freight data that can be used for the implementation of policies towards achieving smart mobility. Because contrary to current practice and dominant discourse, smart mobility is not just a matter of passengers: it also largely relies on more sustainable freight plays an transport. Policy makers see in those new sources of data an opportunity to increase their knowledge on freight transport as well as to have suitable decision support tools to the choices they need to make. In developed countries this trend is illustrated by the increasing requirement of data by recent legislation on freight transport.